PERKEMBANGAN MUSIK KERONCONG DI RICHMOND VIRGINIA AMERIKA SERIKAT - Danis Sugiyanto; Nanang Bayu Aji (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2019)
Keroncong music is music that has an open nature, this can be seen from the history of music development which always receives various developments both from outside the music Keroncong also always develops developments from within in terms of instrumentation and orchestration. Keroncong music not only flourishes and develops in the archipelago but also grows abroad as happened in the United States. The Keroncong Orchestra (OK) Rumput from Richmond Virginia is a group that is steadly spreading the keroncong music culture that is viral in America and the world. Keroncong music is not only studied musically but also forms the basis of cultural learning for its supporters. The concept of collaboration and philosophy in keroncong music helps strengthen world friendship through the humanitarian field.Keywords: keroncong music development, keroncong Rumput orchestra.